2016
DOI: 10.1134/s0362119716010151
|View full text |Cite
|
Sign up to set email alerts
|

Activation of interlimb interactions increases the motor output in legs of healthy subjects: Study under the conditions of arm and leg unloading

Abstract: The effect of arm movements and movements of individual arm joints on the electrophysiological and kinematic characteristics of voluntary and vibration triggered stepping like leg movements was studied under the conditions of horizontal support of the upper and lower limbs. The horizontal support of arms pro vided a significant increase in the rate of activation of locomotor automatism by noninvasive impact on tonic sensory inputs. The addition of active arm movements during involuntary stepping like leg movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Leg movements were accompanied by EMG activity in proximal leg muscles, which were modulated over each movement cycle and displayed similar timing as in normal locomotion (Sylos-Labini et al 2014a). In particular, movement at the shoulder increased activity of hip muscles and amplitude of hip and knee joint movements, whereas and movement of the forearms and wrists had a similar facilitating effect but with a stronger influence on distal segments (Selionov et al 2016).…”
Section: Ipsilateral To Stimulationmentioning
confidence: 87%
“…Leg movements were accompanied by EMG activity in proximal leg muscles, which were modulated over each movement cycle and displayed similar timing as in normal locomotion (Sylos-Labini et al 2014a). In particular, movement at the shoulder increased activity of hip muscles and amplitude of hip and knee joint movements, whereas and movement of the forearms and wrists had a similar facilitating effect but with a stronger influence on distal segments (Selionov et al 2016).…”
Section: Ipsilateral To Stimulationmentioning
confidence: 87%
“…Under terrestrial conditions, in 50-80% of healthy subjects, involuntary movements of the lower extremities can be forcibly evoked by means of vibration stimuli, percutaneous stimulation of the spinal cord, and mechanical stimulation of the supporting zones of the feet [23][24][25][26]. It was previously shown that the interneurons of the L7-S1 segments of the spinal cord, which have inputs from muscle afferents, are activated in different ways by the dorsolateral descending system, which ensures the coordinated work of antagonist muscles during the locomotor cycle [27].…”
mentioning
confidence: 99%